Simplifying the Groundwater Model Interface to Provide Enhanced Decision Support. (29th May 2022) - Craven, John; Adams, Taylor; McCurry, Gordon; Nguyen‐DeCorse, Hong; Scott, Andrew
Abstract: Groundwater modeling can be made more accessible to stakeholders and water managers through interface tools that prepare model inputs and create graphical outputs. An application of this improved modeling technique is presented here, where a model interface tool, called the Groundwater Management Tool (GMT) was developed for the widely used MODFLOW model. The GMT facilitates the evaluation of various water use scenarios for those who have limited time for and/or experience in modifying groundwater model inputs and outputs, yet who need the complexity of a three‐dimensional numerical groundwater model to adequately represent the hydrologic system of interest. The impacts of new pumping wells and altered pumping regimes in existing wells are easily explored through the current version of this interface tool. The modeling technique employed by the GMT provides water managers with the ability to efficiently leverage the decision‐support power and confidence provided by a calibrated groundwater model without the time‐consuming processing of model input and output files, and thereby increases the value and utility provided by the model in supporting water resource management decisions. The purpose of this Technical Note is to highlight an improved modeling approach by combining the power of FloPy with the widely used Microsoft Excel software, to quickly utilize the power of an existing MODFLOW model. Abstract : Research Impact Statement : Interfaces that provide specified, selectable, input parameters for groundwater models facilitate rapid generation of outputs thereby streamlining the decision‐making process for water managers.